Exploring the mechanism of anti-chronic heart failure effect of qiweiqiangxin І granules based on metabolomics - Zhong, Wanru; Li, Yihua; Zhong, Haixiang; Cheng, Yuanyuan; Chen, Qi; Zhao, Xinjun; Liu, Zhongqiu; Li, Rong; Zhang, Rong (Frontiers in Pharmacology, 2023)
Background: Qiweiqiangxin І granules is a traditional Chinese medicine preparation based on the basic theory of traditional Chinese medicine, which produces a good curative effect in treating chronic heart failure. However, its pharmacological effect and potential mechanism for CHF remain unknown. Aim of the study: The purpose of this study is to clarify the efficacy of QWQX І and its possible mechanisms. Materials and methods: A total of 66 patients with CHF were recruited and randomly assigned to the control or QWQX І groups. The primary endpoint was the effect of left ventricular ejection fraction after 4 weeks of treatment. The LAD artery of rats was occluded to establish the model of CHF. Echocardiography, HE and Masson staining were performed to evaluate the pharmacological effect of QWQX І against CHF. Ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry untargeted metabolomics was to screen endogenous metabolites in rat plasma and heart and elucidate the mechanism of QWQX І against CHF. Results：In the clinical study, a total of 63 heart failure patients completed the 4-week follow-up, including 32 in the control group and 31 in QWQX І group. After 4 weeks of treatment, LVEF was significantly improved in QWQX І group compared with the control group. In addition, the patients in QWQX І group had better quality of life than the control group. In animal studies, QWQX І significantly improved cardiac function, decreased B-type natriuretic peptide (BNP) levels, reduced inflammatory cell infiltration, and inhibited collagen fibril rate. Untargeted metabolomic analysis revealed that enriched to taurine and hypotaurine metabolism, glycerophospholipid metabolism and linolenic acid metabolism by KEGG analysis. LysoPC(16:1(9Z)) is a common differential metabolite in plasma and heart, which is produced by lipoprotein-associated phospholipase A2, hydrolyzes oxidized linoleic acid to produce pro-inflammatory substances. QWQX І regulates the level of LysoPC(16:1(9Z)) and Lp-PLA2 to normal. Conclusion: QWQX І combined with western medicine can improve the cardiac function of patients with CHF. QWQX І can effectively improve the cardiac function of LAD-induced CHF rats through regulating glycerophospholipid metabolism and linolenic acid metabolism-mediated inflammatory response. Thus, QWQX I might provide a potential strategy for CHF therapy.